Electrochemical Impedance Spectroscopy - El-Azazy, Marwa; Min, Mart; Annus, Paul (IntechOpen, 2020)
Electrochemical Impedance Spectroscopy is a compendium of contributions from experts in the field of electrochemical impedance spectroscopy (EIS). This compilation of investigations and reviews addresses the groundbreaking applications of EIS in different fields. An array of exploitations are revealed throughout this book such as the use of EIS in monitoring and controlling of corrosion, in medicine where accurate information on fluid distribution is needed as well as environmental applications in food, water, and drug analyses. Competency of EIS as an approach compared to the traditional electrochemical techniques is assessed in almost every application. This book, therefore, is a valuable reference for students, researchers, and anyone interested in electrochemical impedance spectroscopy.